Global serverless videoconferencing over IP - Thomas C. Schmidt and Matthias Wählisch and Hans L. Cycon and Mark Palkow (Future generation computer systems : FGCS, 2003)
In recent years the capabilities of the common Internet infrastructure have increased to an extent where data intensive communication services may mature to become popular, reliable applications. Videoconferencing over IP can be seen as such a highly prominent candidate. However, heavy infrastructure and complicated call handling hinder acceptance of standard solutions.This paper presents a more lightweight framework--both communication scheme and conferencing software--to overcome these deficiencies. A simple, ready-to-use global location scheme for conference users is proposed. First practical experiences are reported.
Keywords: Peer-to-peer videoconferencing; User locating; User address resolution; Multicast videoconferencing; Wavelet transform